MEKTEPKE ShEKEMGI BILIMLENDIRIW ShÓLKEMLERINDE BILIM BERIW OYÍNLARI HÁM OLARDIŃ ÁHMIYETI - Tóremuratova, D.M. (ILIM hám JÁMIYET, 2025)
The article discusses games, which are the main type of children’s activity, and types of games. Educational games and their features, their role in child development are discussed.